Caracterização e mapeamento da vegetação florestal e sua relação com os componentes do relevo na bacia hidrográfica do arroio Caverá oeste do RS/Brasil - Guadagnin, Paula Mirela Almeida (2015)
This paper stresses the existing relationship between the distribution of forest vegetation typologies and forms and relief componentes in the hidrographic basin of the Caverá stream, in the West of the Rio Grande do Sul state, as a subsidy to the discussion of dynamics forest-grassland in that region, using for that geomorphometric variables extracted from SRTM data (Shuttle Radar Topography Mission) and map of vegetation generated through the GIS ArcGIS 10 developed by ESRI, 2013, utilizing images Landsat 8 OLI. This study demonstrated that the relief, through their components, exerts great influence on the distribution and advancement of forest vegetation in predominantly grassland region such as the study area. The hydrographic basin of the Caverá stream, has in its relief, a distinct area of the predominance of the region hills surrounding smooth, that known as Serra do Caverá, has rolling hills and strongly corrugated, with higher declivities that 15% and elevations that reach more than 300 meters. In these portions of the basin, the forest vegetation, principally for capons-of-woods and slopes forests has its most intense occurrence, fact that can be explained by the results obtained in this study. Through the analysis of overlaps and field work in the basin, it was observed that terrain concavities favor, mainly the development of capons-of-wood, whose individuals advanced by the hillsides of hills and morrotes usually through the converging portions of the relief, where there a greater concentration of water, sometimes forming drainage channels. After their establishment on the hillside constituent individuals capons-of-country dissipate also through contacts between volcanic and sandstone rocks, this dynamic occurs constantly until the formation of the slopes forests. The GIS techniques used to study have proved to be appropriate and have allowed the crossing of parameters of the relief and vegetation, demonstrating a important association, especially related to conditions of declivities of slopes and the concentration of water.